Sociolinguistic Influence in the Use of English as a Second Language (ESL) Classroom: Seeing from Onovughe's (2012) Perspective: - Hasanah, Lana; Pradina, Siska; Hadita, Almira; Putri, Wella Cisilya (Universitas Lancang Kuning, 2019)
This paper aims to provide a brief overview and review of the research conducted by Onovughe (2012) under the title Sociolinguistic Input and English as Second Language Classrooms published by the Canadian Center for Science and Education. This article also intended to provide a brief review of the sociolinguistic influences of the use of the second most significant language in the class. Using qualitative descriptive analysis, this study managed to see that OGO’s research used survey within a population of all middle school students in the Akure Ondo Regional Government, Nigeria (n = 240 students). Of the five existing hypotheses, the findings revealed that parents’ occupation is a significant sociolinguistic influence on the use of English among middle school students, followed by gender, age, religion, and classes. This current paper evaluated how Onovughe’s research is represented in his article. Results reveal the strengeths, weaknesses, and the flaws of the article.